Addictive symptoms of mukbang watching: A qualitative interview study using directed content analysis - Kagan Kircaburun; Filipa Calado; Andrew Harris; Mark D. Griffiths (Elsevier, 2024)
Mukbang watching (i.e., watching eating broadcasts) is an emerging online behaviour that has recently gained popularity. Although, there are a number of positive impacts of recreational mukbang watching (e.g., helping overcome loneliness), for a minority of individuals, excessive mukbang watching may turn into problematic (i.e., addictive) mukbang watching and lead to negative consequences. The present study investigated the addictive symptoms of mukbang watching using a qualitative design. The study attempted to determine the addictive symptoms of mukbang watching through semi-structured interviews with a sample of eight mukbang viewers who frequently watched mukbang. Directed content analysis was used to analyse the data. Nine key themes were explored comprising preoccupation, withdrawal, tolerance, inability to stop, loss of interest, continuing despite problems, deceiving family/friends, relieving negative mood, and risking relationships. Findings of the present study concur with those of previous survey research suggesting that mukbang watching may be another online addictive behaviour that can result in adverse consequences for individuals' mental, social, and physical health.